Electrocardiography of laboratory animals - Richig, Jeffrey W. (Elsevier/AP, 2014)
Electrocardiography of Laboratory Animals is the only book covering electrocardiography of laboratory animals, including dogs, mini-pigs, and cynomologus monkeys. As more countries institute requirements for the care of laboratory animals in research, this publication offers an effective standard on performing and analyzing ECGs. Topics covered include safety electrocardiography, toxicology, safety pharmacology, and telemetry. Electrocardiography of Laboratory Animals will assist biological and medical researchers, veterinarians, zoologists, and students in understanding electrocardiography of various species of animals used in research. Covers safety electrocardiography of large laboratory animals. Offers comprehensive analysis of ECGs for practical laboratory use. Includes a self-evaluation section for testing of ECG reading and analysis.